2017
DOI: 10.1149/07540.0029ecst
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Pore Formation in InP: Understanding and Controlling Pore Morphology

Abstract: Pores formed anodically in InP at different temperatures, electrolyte (KOH) concentrations, carrier concentrations and current densities exhibit significant pore width variations. The pore width decreases as the temperature, carrier concentration or current density are increased. The pore width also decreases when the KOH concentration is increased up to 9 mol dm -3 , but increases slightly as the concentration is increased further. These pore width variations are explained by a three-step model for pore forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Each pit leads to a porous domain and, as the domain expands, it blocks the formation of etch pits in that region because the entire domain, including the surface above it, becomes depleted of carriers (with the exception of the pore tips). 61 Essentially then, there is competition between increasing potential, which enables pitting at sites with increasing values of E i , and current-related expansion of porous domains which prevents pitting in the vicinity of existing porous domains; the rate of increase of potential (scan rate) is constant for all experiments but the current is temperature-dependent. As can be seen from Fig.…”
Section: Effect Of Temperature On Surface Pitting and Layer Thickness-mentioning
confidence: 99%
See 3 more Smart Citations
“…Each pit leads to a porous domain and, as the domain expands, it blocks the formation of etch pits in that region because the entire domain, including the surface above it, becomes depleted of carriers (with the exception of the pore tips). 61 Essentially then, there is competition between increasing potential, which enables pitting at sites with increasing values of E i , and current-related expansion of porous domains which prevents pitting in the vicinity of existing porous domains; the rate of increase of potential (scan rate) is constant for all experiments but the current is temperature-dependent. As can be seen from Fig.…”
Section: Effect Of Temperature On Surface Pitting and Layer Thickness-mentioning
confidence: 99%
“…9 where both pore width and pit width are plotted against layer thickness. It is possible 2,61 that the mechanism that controls pit width is to some degree similar to the mechanism which controls pore width and this would explain the correlation between them. Consequently, layer thickness is expected to be correlated with pore width since, as explained above, layer thickness is correlated with pit width.…”
Section: Effect Of Temperature On Surface Pitting and Layer Thickness-mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the dependence on the concentration of acid in a solution of electrolyte was not determined. In research [40], it is reported that dimensions of pores are influenced by various factors, including etching condition and characteristics of the original crystal. However, these data are insufficient to reveal common mechanisms of pore formation and establish the conditions, under which formation of porous structures with specified properties becomes possible.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%